A pilot study comparing ESO-2 capsule endoscopy with conventional upper endoscopy for the assessment of uncomplicated heartburn and dyspepsia. Issue 2 (19th December 2012) - Marelli, Laura; Jaboli, Francesca Maria; Jackson, Linda; Palmer, Hansa; Erian, Gamal; Hamilton, Mark; Epstein, Owen
Abstract : Background: ESO-2 video capsule endoscopy provides images of the oesophageal mucosa and continues to transmit gastric, and often small bowel images, for up to 30 min. This study compares ESO capsule endoscopy capsule oesophago-gastro-duodenoscopy (Cap-OGD) with conventional endoscopy (OGD). Methods: 50 outpatients with uncomplicated dyspepsia underwent Cap-OGD followed by OGD which was recorded on DVD. Cap-OGD and OGD were each reported independently by two gastroenterologists. A benchmark report was also produced by two gastroenterologists viewing both Cap-OGD and OGD on side-by-side monitors. Major findings included large hiatus hernia, Barrett's oesophagus, oesophagitis, erosive gastritis, tumour and ulceration. Minor findings included histologically-proven superficial gastritis, pouting gastric folds and fundic gland polyps. A questionnaire assessed the patient experience. Results: 49 patients completed the study. In 61%, Cap-OGD transmitted in the duodenum. In the benchmark study, all the major OGD findings were observed on Cap-OGD. Cap-OGD revealed fewer minor findings. When reported independently, Cap-OGD and OGD reports indicated differences in interpretation most marked between the capsule readers with or without previous ESO-2 experience. Patients expressed a clear preference for Cap-OGD. Conclusions: When compared side-by-side, all the major findings on OGD are seen on Cap-OGD while there is under-reporting of minor findings. Previous experience of ESO-2 capsule reporting improves reading accuracy and indicates the need for training. This pilot study provides a backdrop to explore the possible role of Cap-OGD, especially where patients are reluctant to undergo conventional OGD or where there is risk of prion contamination of the endoscope.